1967
DOI: 10.1021/j100865a037
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical formation of free radical from hydrogen sulfide, mercaptans, and cysteine

Abstract: Electron spin resonance studies of H2S, CH3SH, C2H5SH, L-cysteine, aqueous solutions of H2S, D2S, CH3SH, CH3SD, and L-cysteine, and L-cysteine in aqueous hydrogen peroxide ultraviolet irradiated at 77°K have been made. The primary photochemical process established for each of these compounds is cleavage of the sulfur-hydrogen bond to yield a hydrogen atom and the corresponding thiyl free radical. For methanethiol in water, the free radicals -CH3 and • CH2SH were identified and evidence that -CH2SH did not come… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…However, when a saturated solution of CH 3 SH in water was frozen and photolyzed at 77 K, ESR analysis revealed the formation of both CH 3 S • and • CH 2 SH (and • CH 3 ). 22 The formation of • CH 2 SH is not easily rationalized by a primary photoprocess, and, at that time, was ascribed to the reaction of a carbon-centered radical with CH 3 SH. However, pulse radiolysis studies have shown that carbon-centered radicals would selectively react with the mercapto group of thiols, 46 and we take the formation of • CH 2 SH during the photolysis of CH 3 SH in water as additional evidence for a (potentially solvent-catalyzed) 1,2-hydrogen transfer in the primary radical CH 3 S • .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when a saturated solution of CH 3 SH in water was frozen and photolyzed at 77 K, ESR analysis revealed the formation of both CH 3 S • and • CH 2 SH (and • CH 3 ). 22 The formation of • CH 2 SH is not easily rationalized by a primary photoprocess, and, at that time, was ascribed to the reaction of a carbon-centered radical with CH 3 SH. However, pulse radiolysis studies have shown that carbon-centered radicals would selectively react with the mercapto group of thiols, 46 and we take the formation of • CH 2 SH during the photolysis of CH 3 SH in water as additional evidence for a (potentially solvent-catalyzed) 1,2-hydrogen transfer in the primary radical CH 3 S • .…”
Section: Discussionmentioning
confidence: 99%
“…Additional support for the possibility of hydrogen abstraction from α-thio-substituted C–H bonds comes from our kinetic NMR experiments on the reaction of cysteamine thiyl radicals with the C γ –H and C ε –H bonds of methionine (Met), 11 and from electron spin resonance experiments on the photolysis of aqueous solutions of CH 3 SH, which resulted in the formation of • CH 2 SH. 22 On the basis of the known photochemistry of thiols/thiolates, any formation of • CH 2 SH via primary photochemical processes appears unlikely, as these result in the cleavage of the C–S or S–H bond, or photoionization (of thiolate), yielding • CH 3 / • SH, CH 3 S • / • H or CH 3 S • /e aq − , respectively (where e aq − represent a hydrated electron). Subsequently, the reaction of • CH 3 , H • and e aq − with CH 3 SH would lead to additional CH 3 S • and • CH 3 but not • CH 2 SH.…”
Section: Introductionmentioning
confidence: 99%
“…20 Additional ESR experiments obtained with small model thiols also suggest the possibility for a formal 1,2-hydrogen transfer in thiyl radicals, i.e. the observation of • CH 2 SH radicals after the photolysis of CH 3 SH, 22 and the detection of CH 3 C • H-SH radicals after photolysis of CH 3 CH 2 SH. 23 …”
Section: Introductionmentioning
confidence: 95%
“…The results of the y-radiolysis experiments are not as clear cut as those for the photolysis, but since many of the products expected or purported to be formed (13,14,34) in y-radiolysis are the same as those found in the photolysis experiment, one can proceed with a certain amount of confidence using the knowledge of the properties of those radicals which are common to both systems and which have been prepared in similar molecular environments. The effects of y-irradiation on glasses such as 3MP have recently been reviewed (2).…”
Section: B Radiolysismentioning
confidence: 99%
“…The effect of radiation or of photolytic absorption on the pure mercaptans has been extensively studied in the gaseous state (11,12), in the solid polycrystalline state (13,14), and in single crystals such as cysteine (15,16). The metastable intermediates of chemical oxidation in dilute aqueous solutions have also been studied using fast flow techniques (17,18), flash photolysis (19), or pulse radiolysis methods (20), but until recently not much work had been done on the radiolysis and photolysis of thlols in dilute rigid solutions using inert or chemically indifferent organic matrices.…”
Section: Introductionmentioning
confidence: 99%